2002
DOI: 10.1007/s00239-001-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Codon and Amino Acid Usage in Thermotoga maritima

Abstract: Abstract. The usage of synonymous codons and the frequencies of amino acids were investigated in the complete genome of the bacterium Thermotoga maritima using a multivariate statistical approach. The GC3 content of each gene was the most prominent source of variation of codon usage. Surprisingly the usage of UGU and UGC (synonymous triplets coding for Cys, the least frequent amino acid in this species) was detected as the second most prominent source of variation. However, this result is probably an artifact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
6
24
0
1
Order By: Relevance
“…In both species of Bartonella the highly expressed genes seem to avoid aromatic amino acids and other large residues in their products as seen in other microbial organisms. 28,29,34 As already mentioned, this observation is compatible with the cost-minimization hypothesis of amino acid usage. 31 Finally, to explore the relationship between protein conservation and gene expression, we have compared the estimated pairwise non-synonymous divergences (d N ) between all orthologues of putative highly and lowly expressed genes pre-identified from the two extremes of axis 1 generated by COA on RSCU of the leading strand genes of two organisms.…”
Section: Relation Between Gene Expression Proteinsupporting
confidence: 87%
See 2 more Smart Citations
“…In both species of Bartonella the highly expressed genes seem to avoid aromatic amino acids and other large residues in their products as seen in other microbial organisms. 28,29,34 As already mentioned, this observation is compatible with the cost-minimization hypothesis of amino acid usage. 31 Finally, to explore the relationship between protein conservation and gene expression, we have compared the estimated pairwise non-synonymous divergences (d N ) between all orthologues of putative highly and lowly expressed genes pre-identified from the two extremes of axis 1 generated by COA on RSCU of the leading strand genes of two organisms.…”
Section: Relation Between Gene Expression Proteinsupporting
confidence: 87%
“…Since the highly expressed genes are mostly located on the leading strand of replication, this observation indicates that proteins encoded by highly expressed genes are preferentially constructed with smaller residues because these residues are energetically less expensive, as were also reported for the proteins in Giardia lamblia 30 and Thermotoga maritime. 29 This indicates that B. henselae and B. quintana, both in spite of their intracellular lifestyle, follow the cost-minimization hypothesis.…”
Section: Major Sources Of Variation In Protein Composition 341 Infmentioning
confidence: 96%
See 1 more Smart Citation
“…This statistical approach has been widely used to investigate major trends in codon usage in several species of bacteria (Grantham et al, 1981;McInerney, 1998;Lafay et al, 1999;Zavala et al, 2002). The position of genes on the main axes generated by the analysis can subsequently be compared with biological properties of the sequences, such as expressivity, base composition, etc., which can help to understand the significance of each main trend.…”
Section: Resultsmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8) With the development of rapid sequencing methods, the genome sequence of prokaryotic organisms, Bacteria and Archaea, have become widely available. Several analyses of the codon-usage bias or the amino acid usage in reference proteomes have been published, such as those of Thermotoga maritima, (9) Pseudomonas aeruginosa, (10) Buchnera species, (11) or the three model prokaryotes Escherichia coli, Bacillus subtilis and Methanococcus jannaschii. (12) These studies revealed remarkable and possibly universal rules that we attempted to relate to the biological function and evolution of the proteins of the organisms of interest.…”
Section: Introductionmentioning
confidence: 99%